Calculation of measurement uncertainty for elasticity module of automobile deadening panels # - AYDEMIR, Bulent; FANK, Sinan (International Journal of Computational and Experimental Science and Engineering, 2016)
All manufacturers need to develop their products applying test to get better performance and higher quality them before distributing the competitive market. In order to get long working life without losing performance of the materials, different tests are applied on the material to determine modulus of elasticity and rupture/deformation stresses using material testing machines. In order to develop repeatable and high quality products, test results should be known very well. The measurement uncertainty of test results should be calculated adding the all influencing parameters during tests. In this study, parameters which have effects on the quality of compression testing are causes the increase measurement uncertainty of test results, Standard measurement uncertainty of modulus of elasticity should be calculated to give reliable results to customer. This study details the work, findings and calculations of the measurement uncertainty of automobile deadening panels after compression testing on the material are presented. Influencing uncertainty parameters on the test results are taken into account and explained in detail.